RANCANG BANGUN WEB PROFIL DESA HUNUTH - Victor Febian Puturuhu (Jurnal Administrasi Terapan, 2026)
Hunuth Village is a village with natural resource potential and public services that require effective information publication media. So far, the delivery of village program information and economic potential is still done conventionally, so the reach of information is limited. This study aims to design and build a web-based information system as the official profile media for Hunuth Village. The system development method used is Waterfall, which includes the stages of requirements analysis, system design, coding, testing, and maintenance. The technologies used include PHP with the Laravel framework and MySQL database. The result of this research is a village profile website that presents information on village history, organizational structure, vision and mission, village potential, and current news features. Based on Black Box testing, the system functions well and is feasible to use. The implementation of this village Kata kunci : Web Profil Desa Hunuth